An analysis on the hurdling techniques of the excellence Chinese male 110m hurdle athletes - Xu ,Y.; Mi, W. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Comparing Chinese male 110m hurdle athlete Liu Xiang with Johnson and Terrence Trammell. The average dividing hurdles time is longer and velocity is lower. The maximum velocity between hurdles is the same but time is less. The time of unsustained phase of Liu Xiang is longer. This shows the problem of striding technique which is the problem of technique and weakness of Liu Xiang. And it's also the key to overtake world advanced level. Liu Xiang's time of three strides between the hurdles is a little better than Johnson and Terrence Trammell. That shows Liu Xiang' frequency of strides is his advantage. Liu Xiang's sprinting ability is a little better than Johnson and Terrence Trammell.